PENERAPAN MODEL PBL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP KELAS VII PADA MATERI HIMPUNAN - Dinda Rahmawati; Aflich Yusnita Fitrianna; M. Afrilianto (IKIP Siliwangi, 2022)
This study aims to apply the Problem Based Learning (PBL) model on students' mathematical problem solving abilities. This research is a classroom action research (CAR). This research was conducted on 21 students Junior Highschool of class VII around Bandung district in the 2021/2022 academic year. The material used is a sets. The instruments used are test and non-test. The test instrument used is a problem-solving ability test in the form of a pretest and a posttest of 5 questions in the form of a description of the set material to determine the effect of the model used with the abilities. The non-test instrument used was a 10-scale interest in mathematics questionnaire which contained negative statements and positive statements. This research was carried out in 2 cycles, each cycle consisting of two meetings. The procedure in this research consists of 1) Plan, 2) Action, 3) Observation, and 4) Reflection. Student learning outcomes in this study obtained N-Gain data in the average category with a score of 0.79 and concluded that the application of the Problem Based Learning model had an effect on the mathematical problem solving abilities Junior Highschool of class VII.